Association of maternal diabetes with attention deficit/hyperactivity disorder (ADHD) in offspring: A meta-analysis and review. (July 2020) - Guo, Dan; Ju, Rong; Zhou, Qifan; Mao, Jinxian; Tao, Hui; Jing, Hui; Zhu, Chen; Dai, Jiazhen
Highlights: This meta evaluates the association of maternal diabetes with ADHD in offspring. Maternal pregestational diabetes increased the risk of ADHD in offspring. Maternal gestational diabetes showed no relation to ADHD in offspring. Abstract: Aims: Researches on the relationship between maternal pregestational or gestational diabetes and attention deficit/hyperactivity disorder (ADHD) in offspring provided inconsistent findings; therefore, we performed an updated and comprehensive literature review and meta-analysis to evaluate the available evidence. Metholds: Relevant articles in Pubmed, Web of Science, Cochrane, Embase, and Wanfang database published until January 2019 were searched without language restriction. We performed a meta-analysis about maternal pregestational and gestational diabetes and risk of ADHD in offspring using odds ratio (OR), relative risk (RR), hazard ratio (HR) and 95% confidence interval (95% CI) extracted from each study. Results: Seven articles were included in this study and a total of 3, 169, 529 participants were accumulated. We found maternal pregestational diabetes increased the risk of ADHD in offspring by 44% (95% CI was 1.32–1.57). Conclusions: Maternal pregestational diabetes is a potential adverse risk of ADHD in offspring. Considering the limited amount of reliable information availabe. In the future, more in-depth and detailed researches, especially population-based prospective cohort studies, are needed to explore this topic more comprehensively.